Cover Journal of Infrastructure & Facility Asset Management - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
Prediction of Rust Thickness in Reinforced Concrete Structures to Enhance the Asset Management for Coastal Infrastructures Wahyuniarsih Sutrisno, I Ketut Hartana & Priyo Suprobo Simulation of Concerete Slab Bevahior to Explosion M. Shabib Al Bari, Januarti Jaya Ekaputri, Faimun, Julendra Bambang Ariatedja, Buntara S. Gan Learning IFAM by using ITS Medical Centre as a Case: #1 - Identifying the Function, Medical Service, Infrastructure & Facility Vita Ratnasari & Hitapriya Suprayitno Potential Number of Passenger and Performance Evaluation of Surabaya School Bus Adhi Muhtadi, Sapto Budi Wasono, Hitapriya Suprayitno & Ervina Ahyudanari Assessment of Infrastructures Assets Induced by Water Level Fluctuation along the Bengawan Solo River T. R. Satrya, R. A.A Soemitro, M. A Maulana, D.D. Wamana & R. Soetanto Road Network Connectivity Quality Assesment for Timor Leste National Road Network Frans de Jesus Babo & Hitapriya Suprayitno